2014
DOI: 10.1186/1754-6834-7-102
|View full text |Cite
|
Sign up to set email alerts
|

Improved sugar co-utilisation by encapsulation of a recombinant Saccharomyces cerevisiae strain in alginate-chitosan capsules

Abstract: BackgroundTwo major hurdles for successful production of second-generation bioethanol are the presence of inhibitory compounds in lignocellulosic media, and the fact that Saccharomyces cerevisiae cannot naturally utilise pentoses. There are recombinant yeast strains that address both of these issues, but co-utilisation of glucose and xylose is still an issue that needs to be resolved. A non-recombinant way to increase yeast tolerance to hydrolysates is by encapsulation of the yeast. This can be explained by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…5D and Table 3). Similar effects have recently been shown by encapsulation of a xylose-fermenting yeast, which led to improved simultaneous consumption of glucose, mannose, galactose, and xylose (19). This can be explained by the same reasoning as for the increased inhibitor tolerance.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…5D and Table 3). Similar effects have recently been shown by encapsulation of a xylose-fermenting yeast, which led to improved simultaneous consumption of glucose, mannose, galactose, and xylose (19). This can be explained by the same reasoning as for the increased inhibitor tolerance.…”
Section: Resultssupporting
confidence: 57%
“…In that study, it was concluded that the tightly packed cell community created by the encapsulation of the cells increases the overall robustness of the yeast by letting cells close to the membrane convert inhibitors, allowing inner lying cells to ferment sugars because of lower inhibitor concentrations. By computer simulations, it has been shown that diffusion limitations in the encapsulated cell pellet lead to concentration gradients of both nutrients and convertible inhibitors (19). It has also been shown that encapsulation of yeast induces a starvation stress response which increases the robustness of the yeast community (11,17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…111,112 Overall, heat-shock resistance in these matrices was similar to that previously reported for alginate-encapsulated S. cerevisiae. 28,113,114 Upon encapsulation and upon entry into stationary phase, yeast ceases to divide, which is accompanied by thickening of their cell wall and accumulation of reserve carbohydrates, both of which help to protect cells from stress. 28,113,114 Upon encapsulation and upon entry into stationary phase, yeast ceases to divide, which is accompanied by thickening of their cell wall and accumulation of reserve carbohydrates, both of which help to protect cells from stress.…”
Section: Cell Escape Increased Over Time Except In Pr Beadsmentioning
confidence: 99%